Exploring Filipino counselors' beliefs about learning - Bernardo, Allan B. I.; Kintanar, Niel Steve M. (2010)
School reform efforts that focus on student learning require school counselors to take on important new roles as advocates of student learning and achievement. But how do school counselors understand the process of learning? In this study, we explore the learning beliefs of 115 Filipino school counselors who indicated their degree of agreement with 42 statements suggested three factors: (F1) social-cognitive constructivist beliefs, (F2) teacher-/curriculum-centered behaviorist beliefs, and (F3) individual difference factors. The preliminary results are briefly discussed in terms of issues related to how Filipino school counselors' conceptions of learning may guide their strategies for promoting student learning and achievement.
Keywords: Students -- Knowledge and learning; Counselors -- Job evaluation